2019
DOI: 10.3390/nano9030373
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Infrared Spectroscopy to Analyze the Interfacial Structures of Ionic Liquids/Al2O3 and Ionic Liquids/Mica Mixtures under High Pressures

Abstract: The interfacial interactions between ionic liquids (1,3-dimethylimidazolium methyl sulfate and 1-ethyl-3-methylimidazolium trifluoromethanesulfonate) and solid surfaces (mesoporous aluminum oxide and mica) have been studied by infrared spectroscopy at high pressures (up to 2.5 GPa). Under ambient pressure, the spectroscopic features of pure ionic liquids and mixtures of ionic liquids/solid particles (Al2O3 and mica) are similar. As the pressure is increased, the cooperative effect in the local structure of pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…In comparison with pure [C 4 MIM][PF 6 ] at the pressure of 0.4 GPa (Figure 2b), the C 2 -H and C 4,5 -H absorption bands of [C 4 MIM][PF 6 ]/DNA mixture at 0.4 GPa (Figure 3b) show smaller frequency shifts under compression. Previous studies [26][27][28] revealed that high pressure can enhance the cluster structure interaction and lead to a band frequency shift. The hydrogen-bond network of an IL cluster structure may be disrupted, as some added molecules (such as DNA) may disturb the associations of ILs or cut large aggregations to small pieces.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…In comparison with pure [C 4 MIM][PF 6 ] at the pressure of 0.4 GPa (Figure 2b), the C 2 -H and C 4,5 -H absorption bands of [C 4 MIM][PF 6 ]/DNA mixture at 0.4 GPa (Figure 3b) show smaller frequency shifts under compression. Previous studies [26][27][28] revealed that high pressure can enhance the cluster structure interaction and lead to a band frequency shift. The hydrogen-bond network of an IL cluster structure may be disrupted, as some added molecules (such as DNA) may disturb the associations of ILs or cut large aggregations to small pieces.…”
Section: Introductionmentioning
confidence: 98%
“…Figure 1a shows two imidazolium peaks at 3124 and 3169 cm −1 , which correspond to the vibrational absorption bands of C 2 -H and C 4,5 -H on the imidazolium ring, respectively [26][27][28]. The other three bands in the region of 2850-3000 cm −1 in Figure 1a are assigned to the alkyl C-H vibrational modes on the cation tail of pure [26][27][28]. The curve fitting and deconvolution of pure ionic liquids spectra were performed with Lorentzian peaks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…High-pressure infrared spectroscopy is a straightforward method to study the adjusted vibrational signals by forcing molecules to come close to each other. Modulating the molecular environments and non-covalent interactions by high pressures may provide special insights into the thermodynamically stable conformations of chemical systems [ 27 , 28 , 29 , 30 , 31 ]. This connotes that, under high-pressure conditions, the IL ions and the PVdF-co-HFP may aggregate at hydrostatic pressures.…”
Section: Introductionmentioning
confidence: 99%